The nature of library automation marketplace among academic libraries in Metro Manila - Laceda, Adora Delle A. (2002)
This study was a survey of the library automation marketplace among academic libraries in Metro Manila. The purpose of this study was to determine the status of library automation marketplace among academic libraries in Metro Manila, specifically to identify the software packages used; and to establish trends in library automation among them.